Importance of extended blood group genotyping in multiply transfused patients - Osman Nadila Haryani, Ahmad Asnawi Asral Wirda, Zulkifli Noor Fadzilah, Othman Ainoon, Sathar Jameela, Leong Chooi Fun, Raja Sabudin Raja Zahratul Azm (Universiti Pendidikan Sultan Idris, 2016)
Importance of extended blood group genotyping in multiply transfused patients by Osman Nadila Haryani, Ahmad Asnawi Asral Wirda, Zulkifli Noor Fadzilah, Othman Ainoon, Sathar Jameela, Leong Chooi Fun, Raja Sabudin Raja Zahratul Azm